E-commerce and data protection legal framework in Malaysia: Lessons from the experiences of the European Union and the United Kingdom - Othman, Mohd Bahrin (2006)
The use of customer data is often an essential part of any business but those involved in E-Commerce in particular make regular use of customer and user personal data for a variety of reasons.Multinational sourcing of data-based tasks is one of the practices that have become widespread as a result of the Internet.Data protection and privacy are a growing legal challenge for policy makers and corporations, as numerous countries have or are considering new laws to protect individual data and privacy. This paper is drawn from an ongoing doctoral research which is aimed at evaluating the state of global data protection legal framework from various regional and national perspectives and identifying a viable model for a comprehensive data protection law viable for Malaysia, that would enable the reconciliation of conflicting interests between the policy maker, organization and society, as well as between individual information privacy and trade interest.Examination into the Malaysian proposed Bill on Personal Data Protection, the European Union’s Directive 95/46/EC and the Data Protection Act in United Kingdom in 1998 will be made.